Impact of Positron Emission Tomography and Endoscopic Ultrasound Length of Disease Difference on Treatment Planning in Patients with Oesophageal Cancer. Issue 11 (November 2017) - Foley, K.G.; Morgan, C.; Roberts, S.A.; Crosby, T.
Abstract: Aims: Treatment decision making and planning in patients with oesophageal cancer are guided by radiological measurement of length of disease (LoD). This study aimed to investigate differences in positron emission tomography (PET) and endoscopic ultrasound (EUS) LoD. Their prognostic significance was also assessed. Materials and methods: LoD was measured from PET and EUS staging investigations by one observer for each modality. Bland–Altman analysis and Wilcoxon signed rank tests assessed agreement and differences in measurements. In terms of radiotherapy planning, the proportion of cases with a clinically significant difference of more than 2 cm between PET and EUS was also calculated. Univariable and multivariable analysis assessed association with overall survival. A P -value < 0.05 was considered statistically significant. Results: Consecutive patients ( n = 160, median age 66.0 years [range 24–83], males = 124, adenocarcinomas = 115) staged with PET/CT and EUS between 2011 and 2014 were included. PET tended to under-measure LoD compared with EUS. The median PET and EUS LoD was 6.4 and 8.0 cm, respectively. PET and EUS LoD was significantly different ( Z = −7.021, P < 0.001). EUS LoD was more than 2 cm longer than PET LoD in 61 cases (38.1%). In eight cases (5.0%), PET LoD was more than 2 cm longer than EUS LoD. Both variables had prognostic significance in univariable analysis, but were not independent predictors of overall survival. Conclusion: There are significant differences in PET and EUS measurement of LoD. This could affect clinical decision making and radiotherapy treatment planning. Clinically significant differences between EUS and PET LoD could lead to a risk of geographical miss in up to 38.1% of cases if the PET/CT measurement alone had been used for radiotherapy planning. These results highlight the continued benefit of EUS in the oesophageal cancer staging and treatment pathway. Highlights: Length of disease is an important measurement in patients with oesophageal cancer. Treatment decision making partly relies on imaging measurements. There are significant differences between measured positron emission tomography and endoscopic ultrasound length of disease. Discrepancies in length of disease have implications for treatment planning.